MELODIOUS: KARYA MUSIK ABSOLUT - Hasibuan, Herindra; Djau, Nurmila Sari; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purposes of the creation of musical works are to 1) offer an innovation and new view in music processing using West Kalimantan traditional music instruments, 2) elevate West Kalimantan culture through sape instrument in melodious musical works so that it is more widely known and worldwide, and 3) become a reference in a musical composition, especially art education in West Kalimantan. The theoretical basis for reference in music creation includes musical composition, elements of musical composition, musical composition techniques, and writing musical notation. This work consists of 4 movements that applies transference, syncretic, and synthesis creation methods. The stages of creation employ several steps which include observation, exploration, composition and evaluation. As an absolute musical work, the discussion and analysis that the author focuses on from each movement lies in the processing of tone and harmony and rhythmic processing. This work is expected to be a reference for music development in West Kalimantan and provide insight for the development of music science, especially the creation of absolute musical works. Keywords: Melodious, Absolute Musical Works, Absolute Music, Music Composition